The Cortisol Response to Hypobaric Hypoxia at Rest and Post-Exercise - Woods, D. R.; Davison, A.; Stacey, M.; Smith, C.; Hooper, T.; Neely, D.; Turner, S.; Peaston, R.; Mellor, A. (Hormone and Metabolic Research, 2012)
High altitude exposure normally leads to a marked natriuresis and diuresis. Acute mountain sickness is often associated with fluid retention, to which an elevated cortisol may contribute. Most investigators report a rise in resting cortisol with ascent, but little data exist regarding the cortisol response to a day trekking. We therefore measured salivary cortisol during ascent to >5 000 m in a cohort of between 42–45 subjects following a 6-h trek (samples taken between 15:30–16:30 h) and between 15–20 subjects at rest (morning samples taken between 08:00–09:00 h). Morning resting cortisol [nmol/l, mean±sd, (range)] was 5.5±2.9 (2.13–13.61) at 1 300 m; 4.7±6.8 (1.4–27.02) at 3 400 m, and significantly (p=0.002) rose between 4 270 m [3.5±2.1 (1.4–8.34)] and 5 150 m [14.5±30.3 (1.9–123.1)]. Post-exercise cortisol [nmol/l, mean±sd, (range)] dropped between 3 400 m [7±6 (1.5–33.3)] and 4 270 m [4.2±4.8 (1.4–29.5)] (p=0.001) followed by a significant rise in post-exercise cortisol between 4 270 m [4.2±4.8 (1.4–29.5)] and 5 150 m [9.2±10.2 (1.4–61.3)] (p<0.001). There were no significant associations between severity of acute mountain sickness and cortisol levels. There was a significant though weak correlation between cortisol post-exercise at 5 150 m and oxygen saturation at 5 150 m (rho= − 0.451, p=0.004). In conclusion, this is the largest cohort to have their resting and post-exercise cortisol levels ascertained at high altitude. We confirm the previous findings of an elevated resting morning cortisol at >5 000 m, but present the novel finding that the cortisol response to a day trekking at HA appears suppressed at 4 270 m.
Keywords: cortisol; hypobaric hypoxia; acute mountain sickness; exercise